Challenging a paradigm: skin sensitivity to sodium lauryl sulfate is independent of atopic diathesis. (1st July 2020) - Heetfeld, A.B.; Schill, T.; Schröder, S.S.; Forkel, S.; Mahler, V.; Pfützner, W.; Schön, M.P.; Geier, J.; Buhl, T.
Summary: Background: Sodium lauryl sulfate (SLS) is the best‐studied detergent in irritant contact dermatitis. In atopic dermatitis, the two major pathophysiological abnormalities concern skin barrier function and regulation of cutaneous immune responses. The probability of atopic skin diathesis can be assessed by comprehensive analysis of patient history, as well as clinical and laboratory findings, resulting in the Erlangen Atopy Score (EAS). Objectives: To investigate the impacts of (i) atopic skin diathesis according to the EAS and (ii) the physician‐assessed diagnoses 'atopic dermatitis', 'allergic rhinitis' and 'allergic asthma' on SLS skin reactions. Methods: This is a retrospective analysis of data from 2030 consecutive patients patch tested with SLS (0·25% aqueous) from two tertiary referral centres in Germany, from 2008 to 2014. Results: Patients with a high probability of atopic skin diathesis showed no significant increase in positive SLS reactions compared with patients without atopic skin diathesis (14·2% vs. 16·8%). The grading of positive SLS skin reactions (1–4) revealed no differences in patients with or without atopic skin diathesis. Furthermore, diagnoses of atopic dermatitis, allergic rhinitis or allergic asthma had no impact on positive SLS skin reactions in multivariate logistic regression analysis. Conclusions: We found no association of increased skin irritability to SLS with atopic skin diathesis, atopic dermatitis, allergic rhinitis or allergic asthma in a large patient cohort. It therefore seems that the test of skin irritability with SLS, which is currently common practice in many centres, does not allow prediction of susceptibility to irritant eczematous inflammation in atopic vs. nonatopic individuals. What's already known about this topic? Irritant contact dermatitis and atopic skin diathesis share impaired skin barrier function as a pathophysiological pattern. Sodium lauryl sulfate (SLS) is tested at 0·25% aqueous as an irritant control in patch testing, and hence the results might be affected by atopic skin diathesis. What does this study add? Challenging a long‐standing paradigm, we found no association of increased reactivity to SLS patch tests in individuals with atopic skin diathesis, atopic dermatitis, allergic rhinitis or allergic asthma in a large patient cohort. Thus, irritant control testing with SLS, which is useful in interpreting doubtful allergen patch test results, does not depend on individual atopy status. Linked Comment: Agner and Elsner. Br J Dermatol 2020; 183 :13 .